2018
DOI: 10.3389/fmicb.2018.01098
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Gene Expression in Yersinia ruckeri: Tracking Specific Genes by Bioluminescence During in Vivo Colonization

Abstract: Yersinia ruckeri is a bacterium causing fish infection processes at temperatures below the optimum for growth. A derivative Tn5 transposon was used to construct a library of Y. ruckeri mutants with transcriptional fusions between the interrupted genes and the promoterless luxCDABE and lacZY operons. In vitro analysis of β-galactosidase activity allowed the identification of 168 clones having higher expression at 18°C than at 28°C. Among the interrupted genes a SAM-dependent methyltransferase, a diguanylated cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…TolC and AcrAB form a tripartite multidrug and toxin secretion efflux pump. Expression of tolC and acrAB in the fish pathogen Yersinia ruckery is increased at 28°C with respect to 18°C with a concomitant increased resistance to antibiotics and toxic substances such as acriflavine [59]. The role of this system in the biology of Pdd remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…TolC and AcrAB form a tripartite multidrug and toxin secretion efflux pump. Expression of tolC and acrAB in the fish pathogen Yersinia ruckery is increased at 28°C with respect to 18°C with a concomitant increased resistance to antibiotics and toxic substances such as acriflavine [59]. The role of this system in the biology of Pdd remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Many Y. ruckeri genes related to virulence were reported to be upregulated at 18°C, similarly as in other fish pathogens (Mendez et al, 2018). These include, among others, genes involved in Osmolarity is an important factor that can influence the expression of virulence genes.…”
mentioning
confidence: 85%
“…A recent study showed a practical approach for identification of virulence . All these genes were previously implicated in virulence (Mendez et al, 2018).…”
Section: Other Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Y. ruckeri is the causative agent of enteric red mouth disease in salmonid fish species (Kumar et al, 2015) and its optimum growth temperature is also 28 • C, while its optimum temperature for infectivity is 18 • C. Similarly, V. anguillarum has an optimum growth temperature of 25 • C whilst the optimum temperature for vibriosis disease is 15 • C (Lages et al, 2019). It appears that a lower temperature optimum for virulence is common in fish pathogens and virulence genes are found to be up-regulated at these lower temperatures (Guijarro et al, 2015;Mendez et al, 2018;Lages et al, 2019). The association of TRL operons with pathogens of poikilothermic hosts (e.g., fish) tempts speculation there is an as yet unknown advantage to this mechanism in such niches.…”
Section: Discussionmentioning
confidence: 99%